2019
DOI: 10.1186/s13578-019-0296-9
|View full text |Cite|
|
Sign up to set email alerts
|

Emerin anchors Msx1 and its protein partners at the nuclear periphery to inhibit myogenesis

Abstract: Background Previous studies have shown that in myogenic precursors, the homeoprotein Msx1 and its protein partners, histone methyltransferases and repressive histone marks, tend to be enriched on target myogenic regulatory genes at the nuclear periphery. The nuclear periphery localization of Msx1 and its protein partners is required for Msx1’s function of preventing myogenic precursors from pre-maturation through repressing target myogenic regulatory genes. However, the mechanisms underlying the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…H3K9me2 and H3K27me3 are the products of G9a ( Shinkai and Tachibana, 2011 ) and EZH2 ( Tan et al, 2014 ), respectively, and inhibition of these HMTs disrupts LAD formation ( Towbin et al, 2012 ; Harr et al, 2015 ). The mechanism of HMT recruitment to LADs remains unclear, but HDAC3 was shown to recruit EZH2 to repressive loci ( Wang et al, 2011 ; Zhang et al, 2012 ; Emmett and Lazar, 2019 ) and emerin was shown to recruit EZH2 and H3K27me3 to the nuclear periphery in C2C12 myoblasts and 293T cells ( Ma et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…H3K9me2 and H3K27me3 are the products of G9a ( Shinkai and Tachibana, 2011 ) and EZH2 ( Tan et al, 2014 ), respectively, and inhibition of these HMTs disrupts LAD formation ( Towbin et al, 2012 ; Harr et al, 2015 ). The mechanism of HMT recruitment to LADs remains unclear, but HDAC3 was shown to recruit EZH2 to repressive loci ( Wang et al, 2011 ; Zhang et al, 2012 ; Emmett and Lazar, 2019 ) and emerin was shown to recruit EZH2 and H3K27me3 to the nuclear periphery in C2C12 myoblasts and 293T cells ( Ma et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…One candidate protein is Msx1. Emerin was shown to bind Msx1 and bridge an interaction between EZH2 and emerin ( Ma et al, 2019 ). G9a was also shown to interact with Msx1 ( Wang and Abate-Shen, 2012a ), so it is possible Msx1 mediates the binding of emerin to HMTs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations